2012
DOI: 10.1111/j.1365-2036.2011.04965.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: probiotics for the treatment of irritable bowel syndrome – focus on lactic acid bacteria

Abstract: SUMMARY BackgroundIrritable bowel syndrome (IBS) is a poorly understood, yet highly prevalent functional gastrointestinal disorder (FGID). The withdrawal, due to adverse events, of a number of pharmacological agents that were approved for the treatment of IBS has left a therapeutic vacuum for patients suffering from the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(130 citation statements)
references
References 102 publications
3
124
0
3
Order By: Relevance
“…Similar to the findings of Moayyedi et al, Clarke and coworkers also showed that despite significant studies heterogeneity in their analysis of 42 randomized-controlled trials, 34 studies reported beneficial effects on at least one pre-specified endpoint including improvement in abdominal pain/discomfort, improvement on abdominal bloating/distension compared to placebo [69]. Both Bifidobacteria and Lactobacilli were found effective in ameliorating IBS symptoms, while the beneficial effects of the multispecies lactic acid bacteria preparations, including the multi-strain preparation VSL#3, were less pronounced.…”
Section: Probioticssupporting
confidence: 64%
“…Similar to the findings of Moayyedi et al, Clarke and coworkers also showed that despite significant studies heterogeneity in their analysis of 42 randomized-controlled trials, 34 studies reported beneficial effects on at least one pre-specified endpoint including improvement in abdominal pain/discomfort, improvement on abdominal bloating/distension compared to placebo [69]. Both Bifidobacteria and Lactobacilli were found effective in ameliorating IBS symptoms, while the beneficial effects of the multispecies lactic acid bacteria preparations, including the multi-strain preparation VSL#3, were less pronounced.…”
Section: Probioticssupporting
confidence: 64%
“…66 More than 40 probiotic intervention studies performed in IBS patients have been published and recently reviewed. [67][68][69][70] In most studies, a strong placebo effect was observed, underscoring the important role that subjective psychological factors play in the response to treatment in these patients. Nevertheless, many of these studies have demonstrated efficacy in improving functional GI symptoms in IBS patients.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Clinicians dealing with this challenge may wish to consider the growing evidence of the importance microbial ecology in human mental and general health, particularly in relation to microbes that: (a) generate the neuroprotective short-chain fatty acids n-butyrate, acetate, and propionate as by-products of their own metabolism [62]; (b) synthesise Menaquinones (vitamin K2) which play an important role in bone remineralisation and calcium regulation – of particular relevance to osteopenia in the elderly [63]; (c) produce indoles such as indolamine-2,3-dioxygenase, which act as catalysing enzymes in tryptophan synthesis, with corresponding beneficial effects on the gut epithelium, but also on serotonin synthesis [64,65]. They might also wish to consider the bacterial species that have been found to upregulate neurotransmitters and neurotransmitter precursors, including GABA, Dopamine, 5HT, and acetylcholine – of particular relevance to mental illness and to neurodegenerative diseases such as Alzheimer’s and Parkinson’s [66].…”
Section: Institutional Coprophagia Todaymentioning
confidence: 99%